(untitled) (Semiárida, 2018)
Horticultural production is carried out under irrigation in the area of Santa Rosa, La Pampa province, where available water sources are highly concentrated in salts. The aim of this study was to evaluate the effect of irrigation with high salt content water on growth, superoxide dismutase (SOD) activity and malondialdehyde concentration, in seedlings of 11 lettuce genotypes. The experiment was performed in a greenhouse, where the seedlings were irrigated for 54 days with two different kinds of water, one from rain as a control and another one of high salinity. Irrigation with high salinity water caused a decrease of 11, 12 and 87% in dry weight yield for Bermella, Grand Rapid and Boltar genotypes, respectively, and a vigor reduction of 2% for Ice 15975 and 3% for Grand Rapid. A the same time, irrigation treatment with high salinity resulted in plant malondialdehyde concentration increases of 56, 98 and 138% for Bermella, Ice 15975 and Grand Rapid, respectively. In the case of the last two genotypes, their response was associated with a SOD activity decrease. The rest of the genotypes did not show changes in malondialdehyde concentration. These results evidenced a differential response among the assayed lettuce varieties, and that malondialdehyde concentration can be used to select genotypes tolerant to irrigation with water of high salt content at seedling stage. DOI: http://dx.doi.org/10.19137/semiarida.2017(02).5966